Recent increases in fatal and non-fatal injury among people aged 65 years and over in the USA. Issue 1 (23rd February 2010) - Hu, Guoqing; Baker, Susan P
Abstract : Objective: To identify recent increases in mortality and morbidity rates from injuries among Americans aged 65 years and over. Design: A longitudinal analysis of mortality and morbidity data on injuries in the elderly, examining variations in recent trends by cause, sex, race/ethnicity and age group. Setting: USA, mortality rate (2000–6) and morbidity rate (2001–7). Data sources: Centers for Disease Control and Prevention's web-based injury statistics query and reporting system online database. Main outcome measures: Linear regression was used to examine the statistical significance of trends in mortality and morbidity rates in the study period. The percentage change in rates was used to measure the linear trend. Race/ethnicity was classified into Hispanic (all races except black), non-Hispanic white ('white') and black. Results: Injury mortality for people aged 65 years and over increased by 3% during 2000–6; morbidity increased by 7% during 2001–7. Falls mortality increased by 42% but emergency department visits for falls did not increase. Significant increases in death rates occurred in motorcycle crashes (145%), machinery (46%), poisoning (34%) and drowning (19%); morbidity rates increased in poisoning (143%), motorcycle crashes (86%), machinery (48%), bicycles (24%), struck by/against (13%) and overexertion (11%). Motor vehicle occupant injuries decreased. Conclusions: The reported rate of fatal falls for people aged 65 years and over increased by 42% during 2000–6 but non-fatal falls did not increase. Research is needed to explain the inconsistent changes between fatal and non-fatal falls, and to identify risk factors contributing to the significant increases in both fatal and non-fatal injuries from machinery, motorcycle crashes and unintentional poisoning.